SIFAT MEKANIK FILM KITOSAN/PVA DENGAN ZEOLIT TERSUBSTITUSI PERAK SEBAGAI KEMASAN AKTIF - Dina Kartika Maharani; Weka Firda Rizki Nurzulla (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2022)
The discussion about adding silver-substituted zeolite on the composite chitosan/PVA has been done with the percentage of silver-substituted zeolite (0,025;0,05;0,1; and 0,2(%w/v)). The ion exchanged between zeolite and silver by immersion method, which is ions Ag+ will doped on to zeolite replace the ions Na+. The Chitosan/PVA films have been obtained are characterized using FTIR and SEM and tested for mechanical properties using Autograph Microcomputer Control Universal Testing. The obtained data indicated that adding zeolite doped with silver increase the mechanical properties of a film. The best mechanical properties showed on addition zeolite/Ag 0,2 (% w/v) with tensile strength 32,733 MPa, elongation at break 42,8%, and modulus young 0,765 Mpa. Functional group identification result by FTIR showed a shift in the O-H and N-H vibration to a lower frequency caused by the addition of zeolite/Ag to the film. Morphological characterization using SEM showed that there are differences on surface morphology between chitosan/PVA before and after the addition of silver-substituted zeolite, Scanning Electron Microscope (SEM) results show there is small particles due to the presence of Zeolit/Ag. Key words: Chitosan, Zeolite, Silver, Mechanical Properties